Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18549/pharmpract.2017.03.948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of targeted educational interventions on appropriateness of stress ulcer prophylaxis in critically ill adults

Abstract: Background:Acid suppression therapy (AST) is routinely used in critically ill patients to prevent stress-related mucosal bleeding (SRMB).Objective:Our objective was to determine the impact of a structured educational intervention on AST used for prevention of SRMB on appropriateness of AST.Methods:A single-center, retrospective, cohort study of appropriate use of AST in critically ill patients admitted to the medical intensive care unit (ICU) at an academic medical center between January to June of 2014 (no in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(76 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…Mechanical ventilation and burn were not found as an indication for SUP in the this study, while some other studies reported so far found mechanical ventilation as a common indication for SUP use. 22,47 This difference may be because our study was conducted at a non-ICU setting where mechanically ventilated patients were less likely to be admitted. In line with our finding, studies by Farsaei et al 19 and Mousavi et al 29 reported that no patient was indicated for SUP due to mechanical ventilation and burn, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation and burn were not found as an indication for SUP in the this study, while some other studies reported so far found mechanical ventilation as a common indication for SUP use. 22,47 This difference may be because our study was conducted at a non-ICU setting where mechanically ventilated patients were less likely to be admitted. In line with our finding, studies by Farsaei et al 19 and Mousavi et al 29 reported that no patient was indicated for SUP due to mechanical ventilation and burn, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flowchart of study inclusion is illustrated in Fig 1 [55]. After screening and determination of eligibility of 14,422 citations, 17 articles published between 2007 and 2019 were ultimately included in the meta-analysis [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. These 17 publications resulted in 16 studies since Buckley et al [65] reported data for both the ICU and non-ICU settings in a single publication and two authors published results of pre-and post-intervention data in separate articles; in the ICU setting: Wohlt et al (pre-implementation) [75] and Hatch et al (post-implementation) [68]; in the non-ICU setting: Khudair et al (pre-implementation) [71] and Khudair et al (post-implementation) [70].…”
Section: Study Inclusionmentioning
confidence: 99%
“…Pavlov et al and Martz et al did not provide any specific exclusion criteria [72,73]. Sample size calculations were conducted by Buckley et al, Hammond et al and Zeigler et al, and all studies included the sample sizes required to determine statistical significance of their respective primary outcomes [65,67,77]. Primary outcomes for each study are listed on Table 1.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations